2001
DOI: 10.1002/1097-4644(20010315)80:4<461::aid-jcb1000>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the protective effects of melatonin and related indoles against ?-naphthylisothiocyanate-induced liver injury in rats

Abstract: The protective effect of melatonin, 6-hydroxymelatonin and N-acetylserotonin against alpha-naphthylisothiocyanate (ANIT)-induced liver injury was investigated and compared in rats injected once with the hepatotoxicant (75 mg/kg body weight). In rats injected with ANIT alone, liver injury with cholestasis developed within 24 h, as indicated by both serum levels of alanine aminotransferase (SGPT) and aspartic acid aminotransferase (SGOT) activities and serum total bilirubin concentration. The administration of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 36 publications
2
54
0
Order By: Relevance
“…In previous investigations conducted by the authors of this study (Darul and Kruczyńska, 2004a,b) no effect of melatonin was observed on the activity of liver enzymes. In contrast, Calvo et al (2001) and Montilla et al (2001) reported a reduction in the enzyme activity in rats with hepatopathy after the injection of the hormone.…”
Section: Resultsmentioning
confidence: 86%
“…In previous investigations conducted by the authors of this study (Darul and Kruczyńska, 2004a,b) no effect of melatonin was observed on the activity of liver enzymes. In contrast, Calvo et al (2001) and Montilla et al (2001) reported a reduction in the enzyme activity in rats with hepatopathy after the injection of the hormone.…”
Section: Resultsmentioning
confidence: 86%
“…Melatonin also has been reported to stimulate the activities of enzymes and increase gene expression that improves the total antioxidative defense capacity of the organism such as SOD, GSH-Px, and GSH (Kotler et al, 1998). Recent studies indicate that MEL is effective on inhibiting oxidative and kidney and liver damage (Calvo et al, 2001). Melatonin also could dose-dependently reduce kidney lipid peroxide content in CCl 4 -treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid peroxidation which can be monitored by measuring the level of liver MDA (Ohkawa et al, 1979) is regarded as one of the basic mechanisms of tissue damage caused by free radicals (Esterbauer et al, 1991). It has been suggested that liver LPO content increases before the formation of liver injury and further increases with the formation and progression of the injury in rats intoxicated once with ANIT Kongo et al, 1999;Calvo et al, 2001;Ohta et al, 2003). The antioxidant enzymes such as SOD, CAT and GPx are the first line of defense against superoxide anion free radicals and hydrogen peroxide mediated injury (Gutteridge et al, 1979;Beck and Levander, 1998).…”
Section: Discussionmentioning
confidence: 99%